INNOVATION IN ECONOMIC THEORY AND THE DEVELOPMENT OF ECONOMIC THOUGHT - Marzena Lemanowicz (Acta Scientiarum Polonorum. Oeconomia, 2015)
The article presents the theory of innovation in the attainment of economic sciences. It reviews the economics literature and looks at the importance of innovation in different economic models. It begins with an analysis of the views of representatives of classical economics, including those of Adam Smith, David Ricardo and Jean-Baptiste Say. This is followed by a discussion of the theory of innovation today, as it is handled in the knowledge-based economy. In analysing the achievements of economic thought, it shows the growing importance of innovation, research and science for socio-economic growth.